Pengaruh konsentrasi minyak sereh wangi, nisbah surfaktan-kosurfaktan, dan kecepatan homogenisasi terhadap karakteristik nanoemulsi minyak sereh wangi [Effect of citronella oil concentration, surfactant-cosurfactant ratio, and speed of homogenization on caracteristics of citronella oil nanoemulsion] - Asmawati Asmawati; Irfan Irfan; Fathia Bilatul Izzah; Agus Riski Anuardi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Lemongrass is a plant that produces essential oils, which contain citronellal, citronellol, and geraniol. These compounds are known to be used as antimicrobials and antioxidants. Nanotechnology is one of the technological innovations that can be used as a medium for sending non-polar active components, such as essential oils. The research was to study the effect of citronella oil concentration, surfactant-cosurfactant ratio, and speed of homogenization on the characteristics of citronella oil nanoemulsion. The research was designed using the Factorial Completely Randomized Design, which consisted of 3 factors. The first factor was the concentration of citronella oil (M1 = 2.5%, M2 = 5%, and M3 = 7.5%). The second factor was the surfactant-cosurfactant ratio (S1 = 1:0, S2 = 3:2, and S3 = 2:3), and the third factor was the homogenization speed (K1 = 6000 rpm and K2 = 12000 rpm). The evaluation research outcome included pH, viscosity, stability, antimicrobial activity, and antioxidant activity. The results showed that the pH value was 4.39 to 5.03 and the viscosity value was 1.00 to 1.28 cP. The resulting nanoemulsion showed no phase separation for 10 days of storage at room temperature. The antimicrobial activity was 6.07 to 6.65 mm. The antioxidant activity of citronella oil nanoemulsion ranged from 74.60-86.73%. Increasing the concentration of citronella oil increased the value of pH, viscosity, antimicrobial activity and antioxidant activity. The highest antimicrobial activity was obtained at the surfactant:cosurfactant ratio (3:2). The antimicrobial activity of the nanoemulsion homogenized at a speed of 12,000 rpm was higher than that of the nanoemulsion homogenized at a speed of 6,000 rpm (P<0.05).